2018
DOI: 10.3390/jcm7090272
|View full text |Cite|
|
Sign up to set email alerts
|

Aerobic Capacity Is Not Associated with Most Cognitive Domains in Patients with Multiple Sclerosis—A Cross-Sectional Investigation

Abstract: (1) Background: Cognitive impairment is highly prevalent in multiple sclerosis (MS). Staying physically fit may be associated with preservation of cognitive performance in persons with MS (pwMS); (2) Objective: To investigate the association between aerobic capacity and the cognitive domains of information processing, learning and memory, and verbal fluency as well as single and composite z-scores of the Brief Repeatable Battery of Neuropsychological tests (BRBNT) in pwMS; (3) Methods: All subjects first perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Previously, we reported absence of baseline correlations between cardiorespiratory fitness and all of the individual tests of the BRB-N in the same sample of pwMS, except for a weak relationship between cardiorespiratory fitness and the composite processing speed Z -score, which includes the SDMT and the PASAT. 24 Here, we present longitudinal cognitive performance data showing no effects of PAE in most tests, in both the total group and in the cognitively impaired group, when compared with waitlist controls. However, according to a clinically meaningful change of 4 points, 30 the cognitively impaired subgroup improved in the SDMT based on the between-group point estimate of +4.9 (–1.3 to 11.1), while the point estimate of the consistent long-term retrieval subtest of the SRT (+7.5 (–0.7 to 15.8)) similarly suggested improvements.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Previously, we reported absence of baseline correlations between cardiorespiratory fitness and all of the individual tests of the BRB-N in the same sample of pwMS, except for a weak relationship between cardiorespiratory fitness and the composite processing speed Z -score, which includes the SDMT and the PASAT. 24 Here, we present longitudinal cognitive performance data showing no effects of PAE in most tests, in both the total group and in the cognitively impaired group, when compared with waitlist controls. However, according to a clinically meaningful change of 4 points, 30 the cognitively impaired subgroup improved in the SDMT based on the between-group point estimate of +4.9 (–1.3 to 11.1), while the point estimate of the consistent long-term retrieval subtest of the SRT (+7.5 (–0.7 to 15.8)) similarly suggested improvements.…”
Section: Discussionmentioning
confidence: 67%
“…Further details on the cognitive performance test protocol in this trial and the seven different tests included in the BRB-N can be found elsewhere. 24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDMT is measure of mental processing speed and not specific to the cognitive deficits such as learning and memory known to commonly occur in MS. Validated MS batteries of cognitive tests exist that might have greater sensitivity to demonstrate efficacy of the interventions (40). Yet newer evidence suggests that mental processing speed may be the cognitive domain best associated with aerobic capacity and best stand-alone cognitive task for MS (14,31)Other study limitations include lack of confounder assessments such as mood and sleep. Finally, the lack of randomized assignment to intervention cohorts tempers the robustness of the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies in MS reveal positive associations between levels of physical activity and walking performance with fatigue, cognitive processing speed, brain volumes, and tract integrity (10)(11)(12). Longitudinal studies of aerobic exercise generally, although not invariably, demonstrate improvements in fitness and MS symptoms (3,13,14). The variations in results may be due to differences between studies in choice of exercise modality, duration, intensity, comparator group activity and outcome measures.…”
Section: Introductionmentioning
confidence: 99%